Testing the reactance vs. the reciprocity of politeness explanations for the effectiveness of the "but you are free" compliance-gaining technique. (2nd April 2016) - Carpenter, Christopher J.; Pascual, Alexandre
Abstract: Two studies were conducted to assess whether reactance or politeness offers a better explanation of the effectiveness of the "but you are free" (BYAF) technique of gaining compliance. The first was conducted with an online survey in the US ( N = 131) and found that the BYAF was associated with lower perceived freedom threat than a control or polite request. The second was a field study and collected data in France ( N = 372), Norway ( N = 360), and the US ( N = 108) to test a 3 (direct request, polite request, or BYAF) × 2 (requester benefits or 3rd party group benefits) design. The BYAF was associated with higher compliance than the other two messages.